Nonverbal post-shot celebrations and their relationship with performance in elite handball - Moesch, K.; Kenttä, G.; Bäckström, M.; Mattsson, C. M. (International Journal of Sport and Exercise Psychology, 2018)
Nonverbal behaviour has an important function in team sports, but research is limited. Adopting a psychological momentum (PM) framework, this study explores the relationship between a team`s history of events, nonverbal post-shot celebrations in the form of gestures and touch shown by the shooter after scoring, and subsequent team performance during handball matches. A naturalistic design with systematic observation was chosen for the present study. Based on an existing coding scheme, 616 post-shot periods from 18 high-stake matches of the highest league in Sweden were analysed. Results showed that the better a team`s prior performance, the more gestures were displayed after scoring in the following period. A high degree of touch when playing well, and a low degree of touch when playing poorly were related to positive subsequent team performance, while, showing much touch when playing poorly, or showing little touch when playing well were related to negative subsequent team performance. The amount of displayed gesture and touch alone was not significantly related to subsequent team performance. To conclude, nonverbal post-shot celebrations were related to subsequent team performance, but only when the ongoing history of events was taken into account, and only for touch. Based on these results, the history of events emerges as an important variable when the dynamics of ongoing team sport matches are investigated. Furthermore, touch, compared to gesture, seems to be of more importance for subsequent team performance. As expected when investigating complex phenomena in ongoing matches, the findings resulted in small effect sizes.